Immobilization of activated carbon on fungal biomass used as bioadsordent for decolorization - Hossain Khan, Mohammad Jakir; Alam, Md. Zahangir; Kabbashi, Nassereldeen Ahmed (2009)
Cost effectiveness, availability and adsorptive properties are the main criteria for choosing the bioadsorbent to remove organic compounds from wastewater. Considering these criteria, an active bioadsorbent was prepared by immobilizing the commercial activated carbon with the fungal biomass through the fermentation process. The potential strains were selected based on immobilization capability through the screening test of different types of fungi. It was observed that the strains Aspergillus niger and Penicillium were able to immobilize 100% activated carbon with its biomass. The immobilized activated carbons on biomass (IACBs) as an active bioadsorbent were characterized by elemental analysis, surface techniques SEM and FT-IR. The functional groups of the bioadsorbent were observed by Fourier transformer infrared spectroscopy (FT-IR). The surface morphology of the bioadsorbent was observed using scanning electron microscopy (SEM). From the characterization study it was observed that significant changes were occurred in surface and structure. The preliminary study on the adsorption of dyes showed significant removal of color in aqueous solution compared to the pure activated carbon. The study shows that the new IACB material might be suitable for the removal of heavy metals or toxic dyes from the industrial wastewater.